Anaerobic Co-digestion of the Organic Fraction of Municipal Solid Waste and the Liquid Fraction From the Hydrothermal Carbonization of Industrial Sewage Sludge Under Thermophilic Conditions - Villamil, John A.; Mohedano, Angel F.; Rodríguez, Juan J.; Borja, Rafael; De la Rubia, M. Angeles (Frontiers in Sustainable Food Systems, 2018)
The anaerobic thermophilic co-digestion of mixtures of the organic fraction of municipal solid waste (OFMSW) and the liquid fraction from the hydrothermal carbonization (LFHTC) of dewatered secondary sludge was studied. Mixtures with a low OFMSW to LFHTC ratio (50, 75, and 100% LFHTC) exhibited accumulation of volatile fatty acids (VFA) as well as low degradation of organic matter and methane production. However, the mixture containing 25% LFHTC performed quite well in terms of methane production: (179 ± 3) mL CH4 STP g−1 CODadded, which was only slightly lower than the value obtained with 100% OFMSW. The experimental results fitted the modified Gompertz model reasonably well and the maximum methane production rate for the mixture containing 25% LFHTC (11.96 mL CH4 g−1 COD d−1) was 29.3% higher than that obtained with the substrate with 100% OFMSW. Therefore, centralized co-digestion of OFMSW in mixtures with 25% LFHTC seemingly provides an effective method for valorizing the latter substrate.